2004
DOI: 10.1002/pbc.20227
|View full text |Cite
|
Sign up to set email alerts
|

Ifosfamide, carboplatin, and etoposide (ICE) reinduction chemotherapy in a large cohort of children and adolescents with recurrent/refractory sarcoma: The Children's Cancer Group (CCG) experience

Abstract: The ORR to ICE reinduction chemotherapy in children with recurrent/refractory sarcoma was 51%. OS of 1 and 2 years appeared significantly improved in patients who had CR or PR following ICE reinduction therapy or who had rhabdomyosarcoma with embryonal histology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 41 publications
2
91
1
2
Order By: Relevance
“…ICE in lower dosages has activity against various solid tumors, [18][19][20][21][22][23][24][25][26][27][28][29][30][31] but it may be particularly suitable for treating NB. Thus, NB is sensitive to all 3 components, whereas other major pediatric solid tumors (eg, Ewing sarcoma) are relatively resistant to platinum compounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ICE in lower dosages has activity against various solid tumors, [18][19][20][21][22][23][24][25][26][27][28][29][30][31] but it may be particularly suitable for treating NB. Thus, NB is sensitive to all 3 components, whereas other major pediatric solid tumors (eg, Ewing sarcoma) are relatively resistant to platinum compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In Children's Cancer Group studies that used higher dosing than previously reported in children (ifosfamide, 9000 mg/m 2 ; carboplatin, 800 mg/m 2 ; etoposide 500 mg/m 2 ), GM-CSF/interleukin-3 fusion protein, 24 G-CSF, 25 and interleukin-6 plus G-CSF, 26 produced no hematologic benefit; and the large patient population included only 2 cases of NB. 27 The studies pointed to a better response rate of refractory or recurrent sarcomas to this ICE regimen compared with lower dose ICE or 2-drug carboplatin-etoposide or ifosfamide-etoposide regimens. 27 Recently, ICE at dosages higher than in preceding phase 1 studies a) was used as salvage, with major responses in 24/64 (36%) patients treated for primary refractory or progressive NB 28 ; and b) was included in induction regimens for patients with newly diagnosed NB with responses defined according to International Neuroblastoma Response Criteria [29][30][31] (Table 3).…”
Section: Toxicitymentioning
confidence: 95%
See 1 more Smart Citation
“…In another study, the combined treatment with carbo platin, ifosfamide and etoposide of children and adolescents with recurrent/refractory sarcomas (including 34 patients with HGOS) appeared to be of moderate efficacy, suggesting further exploration of this drug combination in relapsed patients [81].…”
Section: Pharmacogenomics Of Second-line Drugs In Osteosarcoma Reviewmentioning
confidence: 99%
“…Doxorubicin (ADM) has been reported as an active agent against osteosarcoma (Cortes et al, 1972;Cortes et al, 1974). Carboplatin (CBDCA), a platinum-derived agent, has an anti-tumor activity against osteosarcoma (Meyer et al, 2001;Van Winkle et al, 2005;Daw et al, 2011) Cycle I II III IV V VI VII VIII Week 0 3 6 9 12 15 18 21 Day 1 2 3 1 2 3 1 2 3 1 2 3 1 2 3 1 2 3 1 2 3 1 2 …”
Section: Introductionmentioning
confidence: 99%